Donnie Darko [videorecording (DVD)] - Kelly, Richard, 1975-; Kelly, Richard, 1975-; McKittrick, Sean; Juvonen, Nancy; Fields, Adam, 1965-; Gyllenhaal, Jake, 1980-; Malone, Jena, 1984-; Barrymore, Drew; McDonnell, Mary; Osborne, Holmes, 1952-; Ross, Katharine, 1940- (Twentienth Century Fox Home Entertainment, Inc., 2004)
A high school student must face his dark destiny as delusions bring him face to face with a demonic rabbit who has eerie visions of the past and deadly predictions for the future in this intricate web that will leave you questioning what is real and what is mere hallucination. The director's cut runs about 20 minutes longer than the originally-released version.